Environmental determination of body size in mammals: Rethinking 'island dwarfism' in the golden bandicoot. (17th June 2018) - Dunlop, Judy; Morris, Keith
Abstract: There are several cases of insular animal species exhibiting dramatic differences in body size when compared with mainland counterparts. Such pronounced morphological changes can arise from divergent selection via differing resource availability, competition or predation pressure. Past studies have not been able to demonstrate a reversal of these morphological changes when populations are removed from their island situation. This study examines the body size response of populations of the Barrow Island 'dwarf' subspecies of golden bandicoot ( Isoodon auratus barrowensis : Ramsay, 1887) following translocation to an island and mainland site within their former range. Skeletal and mass measurements, body condition and fecundity of released animals and their offspring were compared to data from the source population. When comparing bandicoots born at translocation sites to source populations, males were significantly larger in skeletal size and mass, females were also significantly larger and exhibited higher reproductive output (number, frequency and average mass of pouch young). These effects occurred in a gradient according to environmental conditions, where animals were smallest and least productive at the densely populated source site, larger and more productive on a nearby island, and largest and most productive at a mainland site with some nutritional supplementation. These changes in skeletal size, mass and fecundity took place in the first 1–4 generations (18 months post‐release), suggesting that the response is not explained by natural selection. We posit that the small size of golden bandicoots on Barrow Island (315.8 ± 4.2 g, this study, cf 569.4 ± 19.3 g, mainland) is not a genotypic response to selective pressures, but rather a reversible phenotypic response to more favourable environmental conditions. A reduction in competitive pressures appeared to allow bandicoots to grow to a larger size and mass, and allow greater reproductive output. Ecological processes relating to resource limitation appear to drive 'island dwarfism' in I. auratus, and may apply to other insular species with morphological differentiation.